A Carotenoid- and Poly-β-Hydroxybutyrate-Free Mutant Strain of Sphingomonas elodea ATCC 31461 for the Commercial Production of Gellan - Ang Li (American Society for Microbiology, 2019)
ABSTRACT Gellan gum is a microbial exopolysaccharide, produced after aerobic fermentation using the Gram-negative bacterium strain Sphingomonas elodea ATCC 31461. Due to its unique structure and excellent physical characteristics, gellan gum has a broad range of applications in food, pharmaceutical, and other industries where it is used for stabilizing, emulsifying, thickening, and suspending. During the fermentative production of gellan, strain ATCC 31461 also accumulates large amounts of the metabolic by-products yellow carotenoid pigments and poly-β-hydroxybutyrate (PHB), which is decreasing the gellan production and increasing processing costs. A pigment PHB-free mutant was obtained by knocking out the phytoene desaturase gene (crtI) in the carotenoid biosynthetic pathway and the phaC gene, encoding a PHB synthase for the polymerization of PHB. Unfortunately, the double gene knockout mutant produced only 0.56 g liter−1 gellan. Furthermore, blocking PHB and carotenoid synthesis resulted in the accumulation of pyruvate, which reduced gellan production. To elevate gellan production, combined UV irradiation and ethyl methanesulfonate (EMS) mutagenesis treatment were used. A mutant strain with the same level of pyruvate as that of the wild-type strain and higher gellan production was isolated (1.35 g liter−1, 132.8% higher than the double gene knockout mutant and 14.4% higher than the wild-type strain ATCC 31461). In addition, a new gellan gum recovery method based on the new mutant strain was investigated, in which only 30% isopropanol was required, which is twice for the wild-type strains, and the performance of the final product was improved. Thus, the mutant strain could be an ideal strain for the commercial production of gellan. IMPORTANCE A carotenoid- and PHB-free double gene knockout strain mutant was constructed to simplify the purification steps normally involved in gellan production. However, the production of gellan gum was unexpectedly reduced. A mutant with 14.4% higher gellan production than that of the wild-type strain was obtained and isolated after employing UV and EMS combined mutagenesis. Based on this high-yield and low-impurity-producing mutant, a new recovery method requiring less organic solvent and fewer operating steps was developed. This method will effectively reduce the production costs and improve the economic benefits of large-scale gellan production.